“Role of Rasanjana Ointment in Napkin Rash" - Bagde, Manjiri; Sheshagiri, Srihari; Damke, Sachin (International Journal of Psychosocial Rehabilitation, 2020)
In Ayurveda, Ahiputana has been described as a condition developed due to improper cleaning of peri-anal region after defecation or after passing urine or after excessive sweating in an neonate/infant. This etiology leads to alleviation of Pitta Dosha and Kapha Dosha leading to itching sensation at that region.In neonates, infancy and early childhood period, children are prone to be sick due to delicate skin and less immunity power.In infants, theof diaper rash ranges from 7 to 35 percent. Diaper rash can develop as early as one week of age, but the peak incidences occurs between 9 and 12 months. To Evaluate the effectiveness of Rasanjana Ointment in napkin rash. The present study is designed as a Randomized comparative controlled open label prospective clinical trial, in which minimum of 15 patients will be enrolled in two groups. In Group A (Standard control) –Ezynapi Ointment will be administered and in Group B (Trial)–Rasanjana Ointment will be administered twice a day for 7 days.Assessment will be recorded on 3, 7th and 14th day. Changes will be observed in subjectiveparameters andobjective parameters outcomes. Suitable conclusion will be drawn post completion of the trial.